Escritura(s) en femenino en las literaturas centroamericanas : Åuna cuestiâon de gâenero? - Perkowska, Magdalena; Mackenbach, Werner (Literature and culture series., 2022)
"From a multifaceted theoretical apparatus and diverse aesthetic proposals, Escritura(s) en femenino en las literaturas centroamericanas reflects on the interrelationships, intersections and differences between women's writing, women's writing(s) and writings in women, in contemporary Central America and its diasporas. Assuming the performative character of both the categories of sex and gender and of writing, the destabilization of binary and essentialist notions and the consequent disconnection between, on the one hand, writing and how it is studied and, on the other, the (supposed) sexual and gender identity. The essays gathered here take up and investigate the fundamental questions of feminist theories and criticism to examine the mobility of the feminine and the masculine in writing, as well as as its cultural and political configurations"--